Meningkatkan Motivasi Berpikir Kritis Model PBL FASE F Materi Hierarki Gereja SMK Negeri 1 Tumbang Titi - Dedi Purnama (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
This research is a classroom action research with Quantitative research method conducted with two cycles. This classroom action research consists of two cycles, each cycle consisting of four stages, namely. planning, implementation, evaluation and reflection. These two cycles were carried out with the aim of knowing PAKat learning outcomes and students' independent thinking motivation.The stages of activities in the form of planning, implementation, observation, analysis, and reflection are carried out face-to-face. Round 1 consisted of two meetings, namely. the first meeting as a discussion of learning objectives and the second meeting as a formative assessment. The procedures and steps of this research followed the principles applied in PTK.The research was conducted at SMK Negeri 1 Tumbang Titi through classroom learning. The subjects in this study were students of class XI of SMK Negeri 1 Tumbang Titi in the odd semester of the 2023/2024 school year, totaling 20 students. The research was conducted using the PBL model with the help of Video. Specifically on the material